THE POTENTIAL OF EVAPORATION BOATS WASTE AS A CRUCIBLE MATERIAL FOR CASTING: A REVIEW - Habiby, M. Nuril Anwar; Rusiyanto, Rusiyanto; Widodo, Rahmat Doni (Indonesian Journal of Engineering and Science, 2024)
Industry in Indonesia continues to experience development in line with advances in science and technology, and this is because the industrial sector makes the most significant contribution to the national economy. However, industrial operations that are getting bigger can produce various kinds of waste, one of which is waste from the processing of plastic metallization applications and modern vacuum coating on food packaging, namely evaporation boats. The result of this waste is substantial because, in its application, evaporation boats will always be used as long as plastic food packaging continues to be produced around the world, so it is necessary to have handling for environmental sustainability in the future. Evaporation boat waste is waste that cannot be decomposed but can withstand heat and be used as a refractory material, especially as a primary material for making crucibles.